Diseño y Validación de Lentes Metálicas (2.4GHz) para el Simulador Satelital en el Laboratorio de Electrónica de la Facultad de Ingeniería - Córdova Ronquillo, Joshua Israel (2023)
A new antenna proposal, designed as a type of metallic lens, using different properties, working at a frequency of 2.4 GHz. A simulated ring will be considered in the electromagnetic software CST Studio and the study of the Characteristic Modes Theory (TMC) using the FEKO software to demonstrate them. Data will be obtained from three types of antennas available in the Satellite Simulator, how they are helical, rectangular patch and logarithmic LPDA, being different from each other, data will be considered reflecting the main radiation parameters (Directivity, Gain, wavelength, etc.). To this proposal, it has been decided to create a new antenna design such as the corresponding lens type, with the main objective of this research project, the comparison of the different radiation parameters as well as the validation of the results, using electromagnetic software such as CST Studio and Feko specialized in obtaining important graphs such as radiation patterns, S parameters, gain, bandwidth, among others. Graphically detailing measured results from a Vector Analyzer (VNA), Spectrum Analyzer, and simulated results from CST Studio for the design of the lens and FEKO for the analysis of characteristic modes. Thus, the satellite trainer that the Electronics laboratory has will have four types of antennas for the proper study and analysis of radiation parameters in a different and didactic way, testing in the same way the quality of both audio and video service that the simulator has. The methodology that will be used for this research work will be quantitative to carry out an analysis of the implementation process of the lenses, to later carry out experimental tests that corroborate that the metallic lenses work at the required frequency, obtaining optimal results within the entire satellite simulation system.